2021
DOI: 10.1038/s41525-021-00255-z
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic truncation variants in ATP9A are associated with a novel autosomal recessive neurodevelopmental disorder

Abstract: Intellectual disability (ID) is a highly heterogeneous disorder with hundreds of associated genes. Despite progress in the identification of the genetic causes of ID following the introduction of high-throughput sequencing, about half of affected individuals still remain without a molecular diagnosis. Consanguineous families with affected individuals provide a unique opportunity to identify novel recessive causative genes. In this report, we describe a novel autosomal recessive neurodevelopmental disorder. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…This disorder is characterized by autosomal recessive hypotonia, ID, ADHD, absent speech, severe receptive language delay, lack of social interactions, and severe sleep disturbance. In addition to the 3 cases we have reported here, the correlation of ATP9A mutations with human neurodevelopmental disorders has recently been reported by 3 groups, although the phenotypes of the patients are partially different [8][9][10], and more individuals with homozygous or heterozygous mutations of ATP9A have mild to severe intellectual disability according to GeneMatcher [47]. Moreover, deficiency and overexpression of ATP8A1-, ATP8A2-, ATP8B4-, and other P4-ATPases are closely related to human neurological diseases, such as ID, hypotonia, hyperkinetic movement disorders, cerebellar ataxia, optic atrophy, hearing loss, autism and Alzheimer's disease [15,[48][49][50][51].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This disorder is characterized by autosomal recessive hypotonia, ID, ADHD, absent speech, severe receptive language delay, lack of social interactions, and severe sleep disturbance. In addition to the 3 cases we have reported here, the correlation of ATP9A mutations with human neurodevelopmental disorders has recently been reported by 3 groups, although the phenotypes of the patients are partially different [8][9][10], and more individuals with homozygous or heterozygous mutations of ATP9A have mild to severe intellectual disability according to GeneMatcher [47]. Moreover, deficiency and overexpression of ATP8A1-, ATP8A2-, ATP8B4-, and other P4-ATPases are closely related to human neurological diseases, such as ID, hypotonia, hyperkinetic movement disorders, cerebellar ataxia, optic atrophy, hearing loss, autism and Alzheimer's disease [15,[48][49][50][51].…”
Section: Discussionsupporting
confidence: 66%
“…Whole exon capture sequencing (WES) showed that this disease may be caused by autosomal recessive inheritance of nonsense variants in ATP9A (NM_006045.3). This gene has not been implicated in any human disease according to OMIM [7] until 2017, but three very recent case reports described that biallelic truncating variants in ATP9A cause neurodevelopmental disorders involving ID, postnatal microcephaly (POM) and Multiple Sclerosis (MS) in humans [8][9][10], providing more evidences for the association between ATP9A and neurodevelopment. However, the clinical relevance and physiological role of ATP9A in the neurological system require further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in P4-ATPase genes are associated with a number of diseases and the fungal genes are becoming linked to pathogenesis. Human P4-ATPase mutations are linked to neurological disease (ATP8A2, ATP9A, ATP8B2, ATP10B, ATP11A), metabolic and cardiovascular disease (ATP10A, ATP10D), cholestasis and hearing loss (ATP8B1), systemic sclerosis (ATP8B4), severe Covid-19 (ATP11A), cancer progression (ATP11B) and hemolytic anemia (ATP11C) (22,23,(32)(33)(34)(35)(36)(37)(24)(25)(26)(27)(28)(29)(30)(31). The P4-ATPase Apt1-Cdc50 from Cryptococcus neoformans transports a variety of substrates, including GlcCer, and is essential in polysaccharide secretion, stress tolerance, fungal survival inside macrophages, and virulence (38)(39)(40)(41).…”
Section: Introductionmentioning
confidence: 99%
“…( 44 ) and updated in Mattioli et al . ( 45 ). Briefly, homozygous and heterozygous variants present in both affected siblings in reported ID genes or potential new ID genes with an MAF <1% and <0.1% in the general population (1000genome, EVS, gnomAD), respectively, were retained.…”
Section: Methodsmentioning
confidence: 99%
“…The overall meandepth base coverage was 136-and 125-fold, while on average 93% and 92% of the targeted region was covered at least 20-fold, respectively. Read mapping and variant calling were performed as described in Alfaiz et al, (2014)(43) and updated in Mattioli et al, (2021)(44).Briefly, homozygous and heterozygous variants present in both affected siblings in reported ID genes or potential new ID genes with a MAF <1% and <0.1% in the general population (1000genome, EVS, gnomAD), respectively, were retained. Their familial segregation was assessed by Sanger sequencing.…”
mentioning
confidence: 99%